THE INFLUENCE OF LEARNING ENGLISH ON PERSONAL WORLDVIEW AND STATEMENTS - Rasuljonov Bekhruzbek Ravshanjon ugli, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article discusses how a person's worldview, beliefs, thinking, and even lifestyle can change through learning foreign languages, the main factors causing this, as well as the negative and positive aspects affecting society. The article analyzes  the  system  for  assessing  the  level  of  a  foreign  language  based  on  world standards, as well as the degree to which the learner's knowledge, skills, and socio-psychological state change at each stage.